Immune response gene profiles in the term placenta depend upon maternal muscle mass. - O'Tierney, P; Lewis, R; McWeeney, S; Hanson, M; Inskip, H; Morgan, T; Barker, D; Bagby, G; Cooper, C; Godfrey, K; Thornburg, K (2012)
Maternal thinness leads to metabolic challenges in the offspring, but it is unclear whether reduced maternal fat mass or muscle mass drives these metabolic changes. Recently, it has been shown that low maternal muscle mass--as measured by arm muscle area (AMA)--is associated with depressed nutrient transport to the fetus. To determine the role of maternal muscle mass on placental function, we analyzed the gene expression profiles of 30 human placentas over the range of AMA (25.2-90.8 cm(2)) from uncomplicated term pregnancies from the Southampton Women's Survey cohort. Eighteen percent of the ∼60 genes that were highly expressed in less muscular women were related to immune system processes and the interferon-γ (IFNG) signaling pathway in particular. Those transcripts related to the IFNG pathway included IRF1, IFI27, IFI30, and GBP6. Placentas from women with low muscularity are, perhaps, more sensitive to the effects of inflammatory cytokines than those from more muscular women.